2012
DOI: 10.1111/j.1525-139x.2012.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Intradialytic Hypotension and Mortality: An Opinionated Review

Abstract: The unchanging rate of symptomatic hypotension that attends maintenance hemodialysis and its link to sodium/volume overload are explored. Correlations between interdialytic weight gain, ultrafiltration rate, hypertension, and mortality are found to be strong. Suggestions/opinions for correcting this unfortunate clinical reality are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 55 publications
1
36
0
2
Order By: Relevance
“…3,4 IDH causes a drop in cardiac output, which may lead to multiorgan dysfunction with an increased risk of myocardial infarction, heart failure, and neurologic complications. [4][5][6][7][8] Several factors might account for the association of IDH with DA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,4 IDH causes a drop in cardiac output, which may lead to multiorgan dysfunction with an increased risk of myocardial infarction, heart failure, and neurologic complications. [4][5][6][7][8] Several factors might account for the association of IDH with DA.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 IDH causes a drop in cardiac output, which may lead to multiorgan dysfunction with an increased risk of myocardial infarction, heart failure, and neurologic complications. [4][5][6][7][8] Several factors might account for the association of IDH with DA. [5][6][7][8][9][10] It has been reported that endothelial dysfunction is associated with IDH due to the effect of dialysis on several serum mediators of the endothelial function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous trials in thrice weekly conventional haemodialysis patients have demonstrated that low dialysate sodium increases risk for intradialytic hypotension [39-41]. However intradialytic hypotension occurs when increases in plasma volume from compartments outside plasma occur slower than haemodialysis reduces plasma volume [40,42]. Our study population had longer haemodialysis duration than previous trials (mean 4.8 hours, interquartile range 3-7 h (Table 1).…”
Section: Discussionmentioning
confidence: 38%